Electrocatalytic nitrogen reduction on defective graphene modulated from single atom catalyst to aluminium clusters - Maibam, Ashakiran; Krishnamurty, Sailaja; BabaRao, Ravichandar (Applied Surface Science, 2023)
Density Functional Theory (DFT) investigation on the most earth-abundant Al-based catalysts, has been conducted detailing its electronic properties and catalytic efficacy for nitrogen reduction at ambient condition. The Al-based catalysts have been modulated to perform as par a highly performing, but rare, Ru-single atom catalytic center by varying number of Al atoms, shape, and size. The coalesce of band-center, work function and electronic properties in metal atom catalysts along with N-N bond activation has been demonstrated to be responsible for an efficient nitrogen reduction reaction (NRR) with Delta Gmax of 0.78 eV in Al5 supported on N-doped double vacancy graphene (Al5@N4-DVG) catalyst. Electron localization function analysis has shown a weak physisorption of N2 in the Al-based catalysts. Projected Density of States (PDOS) illustrates the enhancement of aluminium electron density in Al5@N4-DVG led to enhanced orbital densities overlap of Alp and Np electrons. The Bader charge analysis and electronic analysis of the intermediates show efficient electron gain on the N atoms, leading to formation of NH3 from the NxHy intermediates in Al5@N4-DVG catalyst.